Hegel and Marx in the Times of Globalization - Veljak, Lino (Array, 2014)
In this paper the author try to demonstrate that the basic assumption for understanding the actual events in the world is the conceptualization of the logic of production and the re-production of the world itself. Contrary to a series of ideologically produced and media and publicity mediated false alternatives and mystifications, it’s necessary to embarce the wholiness of the world, in order to be able to tell out mystifications from factually established real tendencies of our epoch. We examined whether the onto-logic, elaborated in the very beginnings of the modern times by «the notorius metaphysicist and declared foe of the common sense» Hegel, can offer methodical and content-adding contributions for the intent of grasping world-historical processes as a whole. Further we discussed the question whether the reconstruction of the logic of reproduction of the modern world, as reconstructed by Hegel’s follower and critic Marx is actually serviceable for such a grasp of wholiness of the world. Besides, there is the question of how much the contradictions of this globalized world depend upon ideologizations of Marx’s concepts and upon the downfall of alleged realization of the ideologicaly disguised Marx’s teachings – and how much of it is the result of nihilistic trends of the era we find ourselves in.